A review of management of early fetal demise in a single centre over a 2-year period. (16th November 2010) - Mathur, M; Shetty, A; Pande, B; Smith, NC; Ashok, PW
Abstract : It is estimated that 15–20% of confirmed pregnancies will spontaneously miscarry. Treatment options for early fetal demise (EFD) include expectant management, medical treatment and surgical intervention in the form of evacuation of retained products of conception (ERPC) under general anaesthetic or manual vacuum aspiration (MVA) under local anaesthetic. Aim of our study was to assess efficacy of treatment options offered to women with EFD. Secondary outcome measures included assessing complications of treatment options. Data was collected prospectively from October 2007 to September 2009, entered and analysed using SPSS 17.0. Selection criterion was diagnosis of EFD in women attending an early pregnancy unit (EPAU). Of the 798 patients diagnosed with EFD, 42.9% (342) women chose medical management, while 7% (56) women opted for expectant management. Half of the women (50.1%) chose surgical management, which included 37.5% (299) opting for evacuation of retained products of conception (ERPOC) and 12.7% (101) MVA. Mean age was 31.4 years (±SD 6.4). Median parity was two (range 0–13). The mean gestation by dates was 74.9 days (±SD 17.6) and scan was 58.9 (±SD 16.5) days. Efficacy of medical management was 89.5% and expectant management was 91%. Efficacy of MVA was 99% and no patients required repeat ERPC. 71% were managed as day cases. 10% of women had early and 0.4% late complications. All of the above treatment options have a high efficacy and low complication rates and should be offered to all women presenting with EFD to an EPAU thereby increasing women's choice of treatment options.